Evaluation of Relevance between Advanced Glycation End Products and Diabetic Retinopathy Stages Using Skin Autofluorescence - Yuji Takayanagi; Mikihiro Yamanaka; Jo Fujihara; Yotaro Matsuoka; Yuko Gohto; Akira Obana; Masaki Tanito (Antioxidants, 2020)
Advanced glycation end products (AGEs) are thought to play important roles in the pathogenesis of diabetic microangiopathy, particularly in the progression of diabetic retinopathy (DR). We assessed the levels of skin autofluorescence (sAF) to assess the association between AGEs and DR stages. A total of 394 eyes of 394 Japanese subjects (172 men, 222 women; mean age ± standard deviation [SD], 68.4 ± 13.7 years) comprised the study population, i.e., subjects with diabetes mellitus (DM) (n = 229) and non-diabetic controls (n = 165). The patients with DM were divided into those without DR (NDR, n = 101) and DR (n = 128). DR included simple (SDR, n = 36), pre-proliferative (PPDR, n = 25), and PDR (n = 67). Compared to controls (0.52 ± 0.12), the AGE scores were significantly higher in patients with DM (0.59 ± 0.17, p < 0.0001), NDR (0.58 ± 0.16, p = 0.0012), and DR (0.60 ± 0.18, p < 0.0001). The proportion of patients with PDR was significantly higher in the highest quartile of AGE scores than the other quartiles (p < 0.0001). Compared to those without PDR (SDR and PPDR), those with PDR were younger (p = 0.0006), more were pseudophakic (p < 0.0001), had worse visual acuity (VA) (p < 0.0001), had higher intraocular pressure (IOP) (p < 0.0001), and had higher AGE scores (p = 0.0016). Multivariate models also suggested that younger age, male gender, pseudophakia, worse VA, higher IOP, and higher AGE scores were risk factors for PDR. The results suggested that AGE scores were higher in patients with DM and were independently associated with progression of DR. In addition, more PDR was seen in the highest quartile of AGE scores. This study highlights the clinical use of the AGE score as a non-invasive, reliable marker to identity patients at risk of sight-threatening DR.